Getting Developmental Science Back Into Schools: Can What We Know About Self-Regulation Help Change How We Think About “No Excuses”? - Bailey, Rebecca; Meland, Emily A.; Brion-Meisels, Gretchen; Jones, Stephanie M. (Frontiers in Psychology, 2019)
Recent research from education, psychology, and human development indicates that social and emotional skills are essential to success in school, work, and life, and that high-quality social and emotional learning (SEL) programs can benefit students’ mental health, academic achievement, and behavioral outcomes. While many schools are adopting an SEL approach, there remains a concerning gap between SEL research and policies and practices related to discipline and behavior management. Following the No Child Left Behind Act and education reform driven by a culture of high-stakes standardized testing and accountability benchmarks, there has been an increase in elementary schools adopting a “no excuses” model of education. This model is characterized by extended time in school, highly structured in-service teacher training, frequent assessments, and “zero tolerance” policies to strictly manage and control children’s behavior. These policies are problematic as they run counter to what research tells us about children’s social and emotional development. Reactive and exclusionary discipline policies inhibit children’s abilities to build and practice self-regulation skills and jeopardize the relationships between students and teachers. The developmental science perspective on children’s regulatory skills suggests that the early years of school are a central context for developing and practicing self-regulation with the support of educators and peers. We also know that warm, caring, reciprocal relationships based on trust are critical to learning and development. Yet, this research base is often overshadowed by pressures to improve standardized achievement scores or misinterpreted in the form of hyper-vigilance about children’s behavior in the classroom. Finally, the “no excuses” approach to behavior management is used disproportionally in schools serving low-income students of color and thus may contribute to unequal rates of suspensions and expulsions, both of which are linked to negative developmental outcomes later in life. This is particularly true for students who have experienced trauma, in part because the act of social exclusion is often re-traumatizing. This article summarizes research on self-regulation, trauma, and developmental relationships, highlights potential consequences of “no excuses” policies and practices in schools, and presents an alternative view of learning environments which promote effective self-regulation skills in young children.